2021
DOI: 10.1021/acs.jpca.1c04048
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Small Oxo/Hydroxo Molecules Containing High Oxidation State Actinides (Th, Pa, U, Np, Pu): A Computational Study

Abstract: The energetics of hydrolysis reactions for high oxidation states oxo/hydroxo monomeric actinide species (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(35 citation statements)
references
References 68 publications
5
30
0
Order By: Relevance
“…This underscores the difficulty of accurately generating actinide energy differences. 101,102 Evaluation of the relative performance of various DFT methods was carried out next, with the results compiled in Table 4. Comparing various DFT approaches to reference CC values produced a set of MDs, MSEs, and MUEs.…”
Section: Pccp Papermentioning
confidence: 99%
“…This underscores the difficulty of accurately generating actinide energy differences. 101,102 Evaluation of the relative performance of various DFT methods was carried out next, with the results compiled in Table 4. Comparing various DFT approaches to reference CC values produced a set of MDs, MSEs, and MUEs.…”
Section: Pccp Papermentioning
confidence: 99%
“…Hunt et al reported a UO 3 –O 2 complex at 842.4 cm –1 in solid argon where O 2 perturbs the strongest UO 3 ν 4 absorption at 852.5 cm –1 . , However, the properties of bonding between UO 3 and O 2 have not been addressed clearly. Several calculations have been carried out on the reactions of the UO 3 molecule with H 2 O and UF 6 . , Unfortunately, the computed results lack experimental support. Accordingly, research on the interaction of UO 3 with other species is expected to provide a new perspective on its reaction and bonding behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental and theoretical researchers have devoted effort to studying the structures, bonding and reactivity of thorium oxide clusters. [7,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Among them, several studies have revealed the stable structures of thorium oxide clusters. [21][22][23][31][32][33]35] Anionic photoelectron spectra combined with theoretical calculations have been carried out to explore the electronic structures and chemical bonding of the gasphase ThO n À /0 (n = 1-3) clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Dixon et al also theoretically studied the reaction mechanism of ThO 2 with H 2 O, and ThO(OH) 2 and Th(OH) 4 were proposed as the hydrolysis products. [24][25][26][27] Although the experimental and theoretical studies of ThO 2 reacting with H 2 O have been reported in the previous studies, the comparison studies on the hydrolysis mechanisms of thorium oxides with the other oxygen contents are still lacked. Additionally, an interesting work on the hydrolysis of the actinide oxides (An=Th, Pa, U, Np, Pu) was recently reported by Dixon and co-workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation